Eco-friendly and miniaturized analytical method for quantification of Rifaximin in tablets - Bersi Motta Correa, Clara; Kogawa, Ana Carolina; Chorilli, Marlus; Regina Nunes Salgado, Hérida (Drug Analytical Research, 2026)
Rifaximin is an oral antimicrobial, semisynthetic and nonabsorbable with minimal adverse effects that act locally in the gastrointestinal tract. Rifaximin does not have standardized methods of analysis for the tablets evaluation in official compendiums. The objective of this study is to develop and validate an analytical method for the quantification of rifaximin in tablets by spectrophotometry in the ultraviolet region, aiming at a miniaturized and eco-friendly method. The method was performed using 700 μL cuvette and purified water: ethanol (4:1, v/v) as diluent. The wavelength used was 233 nm and the range of concentrations was 4-14 µg mL-1. It was linear with correlation coefficient greater than 0.9999, precise with relative standard deviation equal 0.80%, 1.19% and 1.19% for intraday, interday and interanalyst precision, respectively, exact with average recovery of 100.56%, selective against the presence of interferents such as impuruties, matrix compouds and solvents used and robust with the change of ethyl alcohol brand and proportion used as diluent. The method developed presents advantages as, minimum waste generation, reduction in amount of sample, standard and solvents used and reduction in time of analysis. Then this method can be used in rotine analysis of rifaximin tablets as a alternative method, reliable, effective, really fast, low cost, eco-friendly and miniaturized. This study contemplates a current and innovative topic which is extremely important for the area of Quality Control of drugs and medicines and for the sustainable Green Analytical Chemistry.